2022
DOI: 10.1186/s12876-022-02551-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of fecal Helicobacter pylori antigen test in Uganda

Abstract: We evaluated the diagnostic performance of a qualitative stool antigen test (SAT) in individuals with dyspepsia in rural Uganda using the polymerase chain reaction-based 16S ribosomal RNA assay (16S rRNA) for nucleotide sequences for two common H. pylori-associated genes as the reference standard. We enrolled 150 adults with dyspepsia with no self-reported use of antibiotic and/or antiacid medication medications within a fortnight. We performed blinded SAT on fecal specimens and 16S rRNA tests on gastric speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Our study revealed false positive results detected by the SAT exhibited and were negative in gastric biopsies. These results contrasted with a recent study conducted in Uganda, which emphasized the exceptional role of the SAT in detecting H. pylori in regions with a high prevalence of the disease Owot et al [ 24 ] and agreed with the results of Zubair et al [ 33 ] who reported the limited sensitivity and diagnostic accuracy of the HPSA test.…”
Section: Discussionsupporting
confidence: 85%
“…Our study revealed false positive results detected by the SAT exhibited and were negative in gastric biopsies. These results contrasted with a recent study conducted in Uganda, which emphasized the exceptional role of the SAT in detecting H. pylori in regions with a high prevalence of the disease Owot et al [ 24 ] and agreed with the results of Zubair et al [ 33 ] who reported the limited sensitivity and diagnostic accuracy of the HPSA test.…”
Section: Discussionsupporting
confidence: 85%